Treatment patterns, outcomes, and resource utilization of patients with metastatic melanoma in the U.K.: the MELODY study. (1st January 2014) - Lorigan, P.; Marples, M.; Harries, M.; Wagstaff, J.; Dalgleish, A.G.; Osborne, R.; Maraveyas, A.; Nicholson, S.; Davidson, N.; Wang, Q.; Pericleous, L.; Bapat, U.; et al.
Summary: Background: Advanced melanoma is an aggressive disease with a poor prognosis. Approved therapy is limited in the U.K. and, until recently, no treatment had improved survival over best supportive care. A deeper understanding of current clinical practice will help new agents find a place in future treatment pathways. Objectives: To document U.K. clinical practice for the treatment of patients with unresectable stage III/IV (advanced) melanoma. Methods: MELODY (melanoma treatment patterns and outcomes among patients with unresectable stage III/IV disease: a retrospective longitudinal survey) compiled registries of consecutive patients with malignant melanoma (any stage) between 1 July 2005 and 30 June 2006 from France, Italy and the U.K. Patients with advanced melanoma and ≥ 2 months of follow‐up were eligible for analysis. Results: There were 220 eligible patients identified in the U.K., of whom 117 (53·2%) received systemic therapy outside of clinical trials. Over half of these patients received dacarbazine as first‐ or second‐line therapy. Healthcare‐resource utilization was extensive and patients had short survival times: 1‐ and 2‐year survival rates after first‐line systemic treatment were 45·5% [95% confidence interval (CI) 37·1–53·6] and 24·7% (95% CI 17·7–32·3), respectively. Conclusions: Systemic and palliative treatments used to manage advanced melanoma in the U.K. are associated with considerable healthcare resource utilization and poor short‐term survival.